Quality assurance in curricula from the perspective of postgraduate students at Koya University - مصطفى, ا.م.د. خالد إسماعيل مصطفى; رزاق, د. سێبه‌ر رزگار رزاق (Sulaimani Journal for Humanities, 2025)
The aim of this study was to measure the quality assurance process in the curriculum among higher education students at Koya University in general. the sample consisted of 132 male and female students were randomly selected from different departments of the Faculty of Education. The instrument of 30-item was adapted with four dimensions. reliability and validity were at convenience levels. The results showed that there was a statistically significant difference in the measurement of quality assurance in general, which is (0.001). final the study presented several suggestions and recommendations.
Keywords: Quality Assurance; Curriculum; Higher Education; Students Perspective; Higher Education Students